EKSPLORASI ETNOMATEMATIKA PADA JAJANAN KHAS PARIAMAN DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Alfiryani; Fendrik, Muhammad; Antosa, Zariul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Culture is a behavior that is passed down from generation to generation and reflects the identity of a society. In Indonesia, cultural diversity, including traditional snacks, is very important to preserve, especially in the era of globalization which causes many changes in local culture. Typical Pariaman snacks, such as sala lauak, sambareh, lapek koci, and rakik maco, not only have culinary value, but also store mathematical concepts that can be used in learning mathematics in elementary schools. This study aims to explore ethnomathematics in typical Pariaman snacks and the relationship of mathematical concepts in typical Pariaman snacks with mathematics materials in elementary schools. In this study, researchers used a qualitative approach with an ethnographic approach. This research was conducted in Korong Sungai Sariak, Nagari Malai V Suku, Batang Gasan District, Padang Pariaman Regency, West Sumatra and SDN 12 Batang Gasan. Data collection methods in this study are observation in the process of making snacks, interviews with bundo kandung, snack makers, teachers and students at SDN 12 Batang Gasan, and documentation. The results showed that in typical Pariaman snacks there are aspects of ethnomathematics in the form of counting, measuring, designing and explaining activities that contain mathematical concepts, namely the concept of counting operations, the concept of fractions, the concept of comparison, the concept of measurement, and the concept of geometry.